USE OF BROKEN STONE PALU AND SAND PALU ON MIXED AC-BC WITH MARSHALL TEST - NOVIANTI, MAYA (KURVA S JURNAL MAHASISWA, 2016)
Asphalt Concrete is a layer in road construction consists of a mixture of hard asphalt and aggregate having continuous gradation according to the specifications of public works in 2010 revision 3.Â AC-BC is a mixture of pavement layers located under the wear layer (Wearing Course) and at the top of the base layer (Base Course). And has a thickness according to the specifications of 6cm. The purpose of this study to find out the test results marshall use of coarse aggregate of split and sand palu. This study uses a mix design method (the 2010 general job specification revision 3) is carried out in the laboratory using a maximum size of coarse aggregate is 20mm. The sample used for the AC-BC with a variation limit of 21 samples and the middle to upper limit variations in the sample 21 and the total number of 42 samples. Â From the test results marshall AC-BC variation middle limit has a bulk density was 2.342 gr / cm2, void content of the aggregate (VMA) is 16.845%, cavity of mixture (VIM) is 4.386%, the cavity is filled with asphalt (VFA) is 74.237% , stability is 1082.4 kg, flow was 3.6 mm, the rest of the marshall was 97.8%, and the variation upper limit has a bulk density was 2.336 gr / cm2, void content of the aggregate (VMA) is 17.501%, cavity of mixture (VIM) is 4.636%, the cavity is filled with asphalt (VFA) is 73.524%, stability is 848.14 kg, flow is 4.17 mm, the rest of the marshall was 95.9%. Â